무치악 악궁에서 구강과 안면 스캔의 정합을 위한 왁스림의 활용 효과 - 서상혁(Sang-Hyeok Seo); 이청희(Cheong-Hee Lee); 이규복(Kyu-Bok Lee); 김소연(So-Yeun Kim); 이두형(Du-Hyeong Lee) (Journal of dental rehabilitation and applied science, 2024)
Purpose: The purpose of this study was to investigate the accuracy of image merging of an intraoral scan of an edentulous arch to a facial scan using wax rim and markers. Materials and Methods: For registration of oral scan to face scan, a wax rim with markers was made. The markers were cuboid and divided into four groups according to size (5, 10 mm) and attachment location (midline, canine region). The evaluation of registration accuracy was compared with a standard created using cone-beam computed tomography data. Anterior linear variation of the edentulous arch and the 3D variation of the overall arch were measured. Kruskal-Wallis test and Mann-Whitney U test were used for statistics, and the significance level was set at 0.05 and evaluated under Bonferroni correction (0.05/6 = 0.083). Results: In the anterior deviation and global deviation results, there was no statistically significant difference in the oral scan position displacement values between the 5 mm and 10 mm groups. When the midline marker was used, the intraoral scan position displacement value was significantly lower than when only the canine marker was used. Conclusion: Marker attached wax rim can be used for image matching between facial and intraoral scans of the edentulous arch. Marker location at the middle area increases the accuracy of image matching. 목적: 본 연구의 목적은 무치악 악궁에서 마커가 부착된 왁스림을 이용하여 구강 스캔과 안면 스캔을 정합하는 방법의 정확도를 평가하는 것이다. 연구 재료 및 방법: 무치악 환자에서 3차원 가상 환자를 생성을 위해 구강 및 스캔 영상을 촬영하였다. 두 스캔 간의 정합을 위해 마커를 부착한 왁스림을 제작 후 안면 스캔을 획득하였다. 마커는 직사각형 형태로 하였고, 크기(5, 10 mm)와 부착된 위치(정중부, 견치부)에 따라 4개의 군으로 나누었다. 구강과 안면 스캔 간의 병합은 마커를 이용한 점 기반 자동 매칭 방식을 사용하였다. 정합 정확성 평가는 콘빔 컴퓨터 단층촬영 데이터를 이용하여 생성된 기준과 비교하였고, 무치악 악궁의 전방부 선상 변이와 전체적 악궁의 3차원 변이를 측정하였다. 통계에는 Kruskal-Wallis 검정과 Mann-Whitney U 검정이 이용되었고, 유의수준은 0.05로 설정하고 Bonferroni correction (0.05/6 = 0.083)을 반영하여 검증하였다. 결과: Anterior deviation과 global deviation 결과값에서 전체적으로 5 mm와 10 mm인 군 간의 구강 스캔 위치 변위값은 통계적으로 유의한 차이가 없었다. 정중부 마커가 이용된 경우 견치부 마커만 이용된 경우보다 구강 스캔 위치 변위값이 유의하게 낮았다. 결론: 무치악 악궁의 구강 스캔과 안면 스캔 간의 영상 병합을 위해 왁스림을 이용할 수 있다. 마커가 정중부에 있는 경우 정합의 정확도는 향상될 수 있다.